The starfish and the spider : the unstoppable power of leaderless organizations - Brafman, Ori.; Beckstrom, Rod A. (New York : Portfolio, 2006)
Includes information on Alcoholics Anonymous, al Qaeda, Amazon, Animal Liberation Front, Apaches, eBay, General Motors, Goodwill Industries, Google, Grokster, Kazaa, music piracy, Napster, P2P (peer to peer) services, Quakers, record industry, U.S. Supreme Court, Wikipedia, etc.
Introduction -- 1. MGM's mistake and the Apache mystery -- 2. The spider, the starfish, and the president of the Internet -- 3. A sea of starfish -- 4. Standing on five legs -- 5. The hidden power of the catalyst -- 6. Taking on decentralization -- 7. The combo special : the hybrid organization -- 8. In search of the sweet spot -- 9. The new world -- Sources -- Acknowledgments -- Index.
Includes bibliographical references (p. 211-217) and index.
Keywords: Decentralization in management; Organizational behavior; Success in business